When the fly flew in... - Peters, Lisa Westberg; Sneed, Brad (New York : Dial Books for Young Readers, 1994)
Although a young child puts off cleaning the bedroom because all the family's pets are asleep there, the sudden arrival of a zooming fly mysteriously gets the job done.
AD 710
Keywords: Cleanliness -- Fiction; Orderliness -- Fiction; Pets -- Fiction